The correlation between serum neuron-specific enolase level in adult patients of oromaxillofacial fracture with mild head injury - Ruslin, M.; Yusup, HY; Arifin, MZ; Noormartany, N. (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2009)
Oromaxilofacial fracture will have associated with head injury due to its adjacent location and structure. The oromaxillofacial structure is considered to be as force silencer for trauma so that it can protect the intracranial structures. Neuron-specific enolase (NSE) is a specific enzyme within neuron cells and can be detected rapidly in serum. The objective of the study was to investigate the increased serum NSE level in adult patients with oromaxillofacial fracture with mild head injury; and to investigate the correlation between serum NSE level and the location of oromaxillofacial fracture (upper, middle, lower regions, or the combinations) in adult patients with mild head injury. This study used the analytical observational method with a cross-sectional design, that conducted in Department of Neurosurgery, Department of Oral and Maxillofacial Surgery, and Laboratory of Clinical Pathology, Dr Hasan Sadikin Hospital, Bandung, from August to October 2008. The serum NSE level examination was undertaken by blood sample taking then examined with electrochemiluminescence immunoassay (ECLIA). The data were analyzed using Mann-Whitney test to seek the increased serum NSE level; using Kruskal-Wallis to seek the mean of increased serum NSE levels by location of oromaxillofacial fracture; and using Spearman ranked correlation test to seek the correlation between the increased serum NSE levels and location of oromaxillofacial fracture in adult patients with mild head injury. The study results indicated that there was an increased serum NSE level in adult patients with oromaxillofacial fracture with mild head injury by 13.12 ng/mL compared to adult healthy group by 7.72 ng/mL (p<0.001). By upper, middle, and lower regions of oromaxillofacial fracture, the serum NSE level of oromaxillofacial fracture at combined upper-middle-lower region was significantly the highest, i.e., 21.14 ng/mL (p=0.049). A positive correlation between the increased serum NSE level and location of oromaxillofacial fracture caused by mild head injury existed (rs=0.33, p=0.020). In conclusion, there was an increased serum NSE level in adult patients with oromaxillofacial fracture with mild head injury; and there was also a positive correlation between the increased serum NSE level and location of oromaxillofacial fracture due to mild head injury.